Diagnosis of clinically inapparent thyroid carcinoma by immunological examination of its cervicolateral metastasis - Latourrette, Federico; Paseyro, Pedro; Cassinelli, Juan F (Cirugía del Uruguay, 2020)
A new case of thyroid carcinoma not detected on clinical grounds, disclosed by lateral lymph node metastases.